Relasi Nilai Mata Kuliah Tasawuf dengan Akhlak Mahasiswa Institut Agama Islam Tribakti (IAIT) Kediri - Nelsa Arlusi; A. Jauhar Fuad (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2020)
This paper is to answer the relationship between the value of sufism courses with the morals of students. This research is a quantitative approach with field research conducted at IAIT Kediri. Researchers used data collection methods with documentation and distributed questionnaires with a sample of 69 students from 115 students. Research findings, sufism is one of the subjects at IAIT Kediri. Students have high academic grades and a moderate level of morals. Researchers found the relationship between the value of sufism science subjects and the morals of students obtained r count value of 0.139 with a significance of 0.051 so Ha is accepted if using a standard probability of 10%. This means that there is a positive relationship between the value of sufism subjects and the morals of students. The higher the value of sufism courses, the better the morals. Although the magnitude of the correlation coefficient is very weak.